Regime absortivo no World Press Photo : o testemunho fotográfico para além do instante decisivo - Benia, Renata Tavares (2020)
This dissertation examines the absorptive images awarded in the long-form projects category of the World Press Photo. Absorption is the state of mind absorbed in itself or performing some activity in an absorbed, abstracted, concentrated or thoughtful manner, according to Michael Fried (1980). Therefore, the corpus of this study consists of images of absorbed characters located in the long-form projects category in the last 5 years. The objective of this research is to verify how these absorptive themes are explored in relation to the eloquent aspects of the construction of the event; in the temporal and referential relationship (which tend to celebrate the present and immediacy of the event, and high levels of drama in the human pathos). These photographs emerge from a scenario surrounded by visual perceptual wear, from the shock images, saturation of the press clichés and crisis of the production models (POIVERT, 2015). In the countercurrent of this scenario, strategies for temporal and referential reconfiguration of the event emerge. In addition to the decisive bressonian moment and dramatization, these images signal a refusal of objectivity and dramatization, manifesting certain gaps that suggest a possible unrepresentability of the event and fictionality. From this context, our argument is that these imagery constructions have the function of attracting viewers from the perspective of uneasiness and, therefore, mobilize the reader's imagination (in a more attentive and slow reading). Our approach is inscribed in the theoretical currents of aesthetics and art history - to investigate the consequences of the perception of images in journalism. Such dimensions are in congruence with a historical and psychological perspective (CRARY, 2012, 2013), and mental schemes through conventions and stereotypes (GOMBRICH, 1950, 1977). The choice of the analytical properties of this absorptive regime intends to point out the temporal, dramatic (human action and physiognomy) and aesthetics intertwined, in order to understand how absorption is manifested in different photographic essays, and what are the repercussions. Therefore, we will analyze these images based on the concept of absorption formulated by art historian Michael Fried (1980). Given this scenario, it is essential to discuss the exercise that has been noticed in the space of institutional photojournalism, based on attempts that break with the recognizable visual tropes (drama and action), which seek a more contemplative and attentive content (at the same time that revive certain currents of art history). By transcending the decisive moment, these images reverberate consequences in the referential and temporal reading of photojournalism and in the perceptual habits of visual culture (from the aesthetic, imaginative and slowed-down experimentation of the gaze).